2015
DOI: 10.1002/app.42919
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility, steady and dynamic rheological behaviors of polylactide/poly(ethylene glycol) blends

Abstract: Understanding the rheological behavior of plasticized polylactide (PLA) contributed to the optimization of processing conditions and revealed the microstructure–property relationships. In this study, the morphological, thermal, steady and dynamic rheological properties of the PLA/poly(ethylene glycol) (PEG) blends were investigated by scanning electron microscope, differential scanning calorimeter, and capillary and dynamic rheometers, respectively. The results illuminated that the melt shear flow basically fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…This finding was due to PEG acting as a macromolecular plasticizer and increasing the free volume of polymer chains, which weakened the degree of chain entanglement. However, at 1.5 wt % OMMT, the end of the arc rose, a new Cole–Cole radius emerged, and a new relaxation behavior was found, showing that the single layer of slices formed a rigid inorganic particle network structure …”
Section: Resultsmentioning
confidence: 99%
“…This finding was due to PEG acting as a macromolecular plasticizer and increasing the free volume of polymer chains, which weakened the degree of chain entanglement. However, at 1.5 wt % OMMT, the end of the arc rose, a new Cole–Cole radius emerged, and a new relaxation behavior was found, showing that the single layer of slices formed a rigid inorganic particle network structure …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, when the PEG‐10000 content was 20 wt%, the most efficient plasticizing effect was obtained. In another study of Li et al ., in which PEG ( M w = 6000 g mol −1 ) was incorporated in PLLA at 5, 10, 15 and 20 wt% via melt‐extrusion, the single glass transition temperature ( T g ) and the significant reductions in T g and cold crystallization temperature ( T cc ) of the PLLA/PEG blends demonstrated that PEG was miscible with PLLA when the PEG content was less than 10 wt%. By comparing the small melting peaks of PEG observed in the PLLA/PEG blends when PEG was incorporated at 15 and 20 wt% to that of pure PEG, it was suggested that the PEG phase might have been separated from the PLLA/PEG blends.…”
Section: Introductionmentioning
confidence: 99%
“…Among the thermoplastic aliphatic polyesters, poly( l ‐lactic acid) (PLLA) presents excellent biodegradability, biocompatibility and bioresorbability along with transparency and low toxicity . Standard‐grade PLLA is also characterized by high modulus and strength but is brittle and rigid in nature with poor toughness and low melt strength which lead to difficulties in demoulding .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly (lactic) acid (PLA) is biodegradable aliphatic polyester, which can be fabricated by fermentation of renewable resources such as corn, cassava, potato and sugarcane [1,2]. Comparison to other aliphatic polyesters, PLA has perfect attributes such as high mechanical strength, high modulus, biodegradability, biocompatibility, bio absorb ability, transparency, energy savings, low toxicity and easy process ability [3,4]. Moreover, PLA has a wide range of applications such as in agricultural films, biomedical devices, packaging, and automotive industries due to its great properties [5][6][7].…”
Section: Introductionmentioning
confidence: 99%